In your dreams : cultural appropriation, popular culture and colonialism - L. Behrendt (Law Text Culture, 1998)
Industrialisation, globalisation, technological advancement, urbanisation, mass communication systems and other sources of modernity have created a society with contradictions. As much as these elements offer the individual interconnectedness with others, a plethora of opportunities, the ability to transcend gender, racial, cultural and geographical boundaries they also contribute to an impersonal society whose members complain of alienation and a spiritual hunger that capitalistic fetishism cannot seem to satiate. Little wonder then that interest in eastern religions, the occult, psychic networks and fundamentalist religions is on the rise. In this quest for reassurance and clarity, people have also sought to find the mythic and the spiritual in indigenous cultures.